Fire evacuation strategies for traditional public markets in an aging society - Chih-Hao Hsu; Carol C. Wu; Kai-Min Liao (Case Studies in Thermal Engineering)
Traditional public markets in Taiwan are unique in that they mimic markets in traditional agricultural societies, offering convenient access to diverse goods and services. Many are in enclosed indoor spaces and have vendors that provide complex services requiring kitchens or other equipment; this increases both crowding and fire risk. They have few entrances and exits, densely packed stalls, narrow walkways, and poor signage. These all suggest a high risk of a crowd crush accident during an emergency evacuation, and effective improvements are urgently needed. In this study, improvements to evacuations were investigated through spatial dynamic simulation. A representative two-floor market was modeled, and on-site surveys were performed to identify customer behavior and demographics. The fire simulation software PyroSim was used to simulate a fire in the market to identify the maximum evacuation time before safe temperature, smoke, carbon monoxide, or visibility limits were exceeded. The collected on-site data were used to simulate an evacuation for a crowd with pedestrians of various ages and genders in Pathfinder software. The evacuation time, crowd density, and exit signage were evaluated, and improvements based on the results were proposed and validated.